Changes in mental health and drug use among men who have sex with men using daily and event-driven pre-exposure prophylaxis: Results from a prospective demonstration project in Amsterdam, the Netherlands - R.C.A. Achterbergh; E. Hoornenborg; A. Boyd; L. Coyer; S.J.A. Meuzelaar; A.A. Hogewoning; U. Davidovich; M.S. van Rooijen; M.F. Schim van der Loeff; M. Prins; H.J.C. de Vries (EClinicalMedicine, 2020)
Background: Gay, bisexual and other men who have sex with men (GBMSM) are at increased risk of mental health disorders and drug use. In GBMSM taking pre-exposure prophylaxis (PrEP) for HIV, the proportion engaging in risk behaviors could increase due to decreased perception in HIV risk. In turn, this could leave them further susceptible to mental health disorders. Methods: The AMsterdam PrEP study (AMPrEP) is a demonstration project offering a choice of daily PrEP or event-driven PrEP regimen at the STI clinic of the Public Health Service of Amsterdam. Eligible participants were HIV-negative GBMSM and transgender people at risk of HIV, aged ≥18 years. We assessed anxiety and depressive mood disorders (Mental Health Inventory 5), sexual compulsivity (Sexual Compulsivity Scale), alcohol use disorder (Alcohol Use Disorder Identification Test), and drug use disorder (Drug Use Disorder Identification Test) using yearly self-administered assessments (August 2015–September 2018). The proportion of mental health problems were analyzed and changes over time and between regimen were assessed using a logistic regression model. Variables associated with the development or recovery of disorders were assessed using a multistate Markov model. Outcomes: Of 376 enrolled, we analyzed 341 participants with data at baseline and at least one follow-up visit. During a median follow-up of 2.5 years (IQR=2.3–2.7), the proportion assessed with sexual compulsivity decreased from 23% at baseline to 10% at the last visit (p<0.001) and drug use disorder decreased from 38% at baseline to 31% at the last visit (p = 0.004). No changes occurred in proportion assessed with anxiety/depressive mood disorders (20% at baseline, 18% at last visit, p = 0.358) or alcohol use disorder (28% at baseline, 22% at the last visit, p = 0.106). During follow-up, participants reported significant less use of alcohol (p<0.001), nitrites (p<0.001) and ecstasy (p<0.001). We found no differences between daily and event-driven PrEP users. The development and recovery of disorders during follow-up were highly interrelated. Interpretation: Mental health disorders are prevalent among those initiating PrEP. We did not find increases in mental health disorders during PrEP use, but rather a decrease in sexual compulsivity and drug use disorders. The initial prevalence of mental health disorders in our study point at the continuous need to address mental health disorders within PrEP programs. Funding: ZonMw, H-TEAM, Internal GGD research funds, Aidsfonds, Stichting AmsterdamDiner Foundation, Gilead Sciences, Janssen Pharmaceutica, M A C AIDS Fund, and ViiV Healthcare.